2020
DOI: 10.1111/epi.16444
|View full text |Cite
|
Sign up to set email alerts
|

Early epilepsy in children with Zika‐related microcephaly in a cohort in Recife, Brazil: Characteristics, electroencephalographic findings, and treatment response

Abstract: Objective To estimate the incidence of epilepsy in children with Zika‐related microcephaly in the first 24 months of life; to characterize the associated clinical and electrographic findings; and to summarize the treatment responses. Methods We followed a cohort of children, born during the 2015‐2016 Zika virus (ZIKV) epidemic in Brazil, with congenital microcephaly and evidence of congenital ZIKV infection on neuroimaging and/or laboratory testing. Neurological assessments were performed at ≤3, 6, 12, 15, 18,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
65
2
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 40 publications
4
65
2
2
Order By: Relevance
“…It is not possible to determine whether the condition was resolved or if this behavior was modi ed by the frequent use of anticonvulsants in this population. 31 Also unexpectedly, children without microcephaly (Groups 3 and 4) demonstrated high frequencies of risk signs of behavioral and emotional symptoms (42.5% and 63.7%, respectively). Although the underlying cause in this cohort is currently unknown, we note that studies have shown a progressive increase of the prevalence of behavioral abnormalities in childhood worldwide [32][33][34] .…”
Section: Discussionmentioning
confidence: 92%
“…It is not possible to determine whether the condition was resolved or if this behavior was modi ed by the frequent use of anticonvulsants in this population. 31 Also unexpectedly, children without microcephaly (Groups 3 and 4) demonstrated high frequencies of risk signs of behavioral and emotional symptoms (42.5% and 63.7%, respectively). Although the underlying cause in this cohort is currently unknown, we note that studies have shown a progressive increase of the prevalence of behavioral abnormalities in childhood worldwide [32][33][34] .…”
Section: Discussionmentioning
confidence: 92%
“…It is not possible to determine whether the condition was resolved or if this behavior was modi ed by the frequent use of anticonvulsants in this population. 31 Also unexpectedly, children without microcephaly (Groups 3 and 4) demonstrated high frequencies of risk signs of behavioral and emotional symptoms (42.5% and 63.7%, respectively). Although the underlying cause in this cohort is currently unknown, we note that studies have shown a progressive increase of the prevalence of behavioral abnormalities in childhood worldwide [32][33][34] .…”
Section: Discussionmentioning
confidence: 92%
“…8,9 Due to the nature and severity of injuries to the CNS, epilepsy is a frequent finding and may lead to clinical deterioration. [10][11][12] Most clinical descriptions of CZVS are based on infants at an early age. At this stage of life, epilepsy occurs in 58.3%-71.4%.…”
mentioning
confidence: 99%
“…[10][11][12] Epileptic spasms are the primary type of seizure during the first year of life, 11 whereas focal motor seizures prevail in the second year. 12 Despite the abundance of clinical data, in-depth descriptions of the electroencephalographic (EEG) pattern are scarce. 12 According to earlier studies, hypsarrhythmia, focal, and multifocal epileptiform discharges (ED) frequently occur in this phase of life.…”
mentioning
confidence: 99%
See 1 more Smart Citation